KARAKTERISTIK FISIKOKIMIA DAN FUNGSIONAL PATI HIDROTERMAL UBI JALAR UNGU - Firstyarikha Habibah; Sedarnawati Yasni; Sri Yuliani (Jurnal Teknologi dan Industri Pangan, 2018)
Starch is a processed product from sweet potato widely used in foods product.  However, in general native sweet potato starch has constrains that often inhibits its application in food products. Starch hydrothermal modification might overcome the problem. This study aimed to study the effect of hydrother-mal treatment on the physicochemical and functional characteristics of purple sweet potato starch. The study was conducted in two stages, i.e. modification of starch purple sweet potato variety antin-3 hydrothermally, i.e. using moisture content of 30, 50% and heating temperature of 55 and 75°C, and characterization of the physicochemical and functional properties of the modified starch. The yield of starch from purple sweet potato by wet extraction method was 16.81±1.48%. Hydrothermal treatment on the purple sweet potato starch did not alter the concentration of starch, amylose and amylopectin. The natural and hydrothermal starches had polygonal granular shape. The swelling power of the hydrothermal starch incubated at 75°C was higher than that of incubated at 55°C, while the hydrothermal starch solubility was lower than the natural starch. The natural and hydrothermal starches of purple sweet potato had an A-type starch gelatinization profile. Hydrothermal treatment of starch with 50% moisture content at 75°C could change the functional properties of starch, i.e increased the proportion of slowly digestible starch by 22%.